Is the new "new" digital journalism a type of activism? An analysis of "Jot Down", "Gatopardo" and "The New Yorker" (Communication & Society, 2019)
Digitization and the economic crisis have led journalism to a new paradigm (Albalad, 2018). Contents and customs have changed, supporting media has changed, new journalistic models are hybrids and the mainstream media do not always deal with the issues that society demands (Sims, 2018). With a knowledge of tradition, but following the path of innovation, narrative journalism emerges as a possible response to this state of affairs. The objective of this analysis is to identify the challenges facing narrative journalism and narrative journalists themselves in this regard. We analyse their formats, routines and content, study how their digitally existence (Drok & Hermans, 2016) and ask ourselves if they constitute a platform for journalistic activism. Three magazines were identified for the selection of case studies: Jot Down, Gatopardo and The New Yorker. Their digital models, content and literary quality are the principal reasons for their selection, in addition to their different seniorities, geographical backgrounds and formats. By deploying a qualitative research methodology based on content analysis (Voutsina, 2018), in-depth interviews (Johnson, 2002), non-participant observation and document review, this analysis suggests that the new new digital journalism is a kind of activist journalism that upholds the traditions of reporting, narrative journalism and literary quality. This study is based on two theoretical premises: narrative journalism, exemplified by authors such as Sims (1996) and Herrscher (2012) and digital journalism, represented by writers such as Rost (2006) and Domingo & Heinonen (2008).